Kewajiban Surat Tanda Terdaftar (STT) bagi Notaris sebagai Profesi Penunjang Sektor Keuangan berdasarkan Undang-Undang Nomor 4 Tahun 2023 - Vicky Perdana (Jurnal Hukum dan Sosial Politik, 2025)
Chapter 2 POJK Number 67/POJK.04/2017 concerning Notaries with Activities in the Capital Market requires that Notaries with activities in the Capital Market must obtain a Certificate of Registration (STT) by the OJK. After the PPSK Law, Notaries are also declared a Financial Sector Supporting Profession and must be registered by the relevant minister, institution or authority. The problems are: (1) How are financial sector supporting professions regulated based on Law Number 4 of 2023? (2) What are the Obligations of a Notary as a Financial Sector Supporting Professional in obtaining a Registration Certificate (STT) Based on Law Number 4 of 2023? The method used in this research is Normative Juridical, with data collection through literature study. The research results show that professions supporting the financial sector, including notaries, are required to be registered by the Financial Services Authority and Bank Indonesia, but there are still no regulations governing the registration procedures.